PENGHENTIAN PERKARA PENYALAHGUNAAN NARKOTIKA DI TINGKAT PENYIDIKAN BERDASARKAN KEADILAN RESTORATIF - Riza Chatias Pratama; Aldisa Melissa (Jurnal Interpretasi Hukum, 2024)
Narcotics crime is one of the most frequent crimes among cities in Indonesia.  Drugs (psychotropics, narcotics and other addictive substances) are certainly something that endangers human life by the inappropriately used, due to the dependency cause and even result in an overdose. Narcotics abuse is a global problem, and no longer just limited to regional and national problems in Indonesia. Narcotics abuse has penetrated public spaces and even carried out by men and women without any debate about gender, economic class or even age. The increasing numbers of narcotics abuse leads to criminal acts which can result in criminal sanctions. However, currently the resolution of criminal acts of narcotics abuse is no longer limited to criminal sanctions or even efforts to imprison the perpetrator. After the issuance of National Police Chief Regulation Number 8 of 2021 on Handling of Criminal Acts Based on Restorative Justice, the resolution of narcotics abuse cases that meet the criteria as stipulated in this regulation can be given action sanctions in the form of rehabilitation. The implementation of the National Police Chief's regulations in the Aceh Regional Police Legal Area has been implemented and has succeeded in resolving 4 (four) cases of narcotics abuse through restorative justice. Overall, the implementation of the this regulations is appropriate but not yet effective because only a small number of cases are resolved using restorative justice.